Ultraviolet Absorbing Efficacy and Photostability of Feruloylated Soybean Oil. (7th May 2018) - Compton, David L.; Goodell, John R.; Evans, Kervin O.; Palmquist, Debra E.
Abstract: Feruloylated soy glycerides (FSG) are a natural‐based, ultraviolet (UV) absorbing, antioxidant vegetable oil synthesized from the lipase‐catalyzed transesterification of ethyl ferulate and soybean oil. Commercial broad spectrum UV absorbing formulations contain multiple UV absorbing compounds that absorb UV radiation in specific regions. The most commonly used compounds are avobenzone (AVO, λ max 356 nm) and octinoxate (ONX, λ max 310 nm), which absorb primarily ultraviolet A and ultraviolet B radiation, respectively. The FSG chromophore is chemically similar to ONX but has a λ max of 328 nm, approximately the median λ max of AVO and ONX. Equimolar mixtures of AVO–ONX and AVO–FSG, 50 μM:50 μM, solutions in ethanol were compared to determine whether FSG was fungible for ONX in total absorbance capacity, photostability when exposed to UV radiation, and broad spectrum absorbance coverage before and after exposure to UV radiation. While it was determined that AVO–FSG mixtures possessed statistically indistinguishable total absorbance capacity compared to AVO–ONX solutions, AVO–FSG possessed slightly better photostability after 4 hours of UV exposure based on 95% confidence interval comparisons from weighted regression equations. Substituting FSG for half of the ONX (e.g., 50 μM:25 μM:25 μM AVO–ONX–FSG) resulted in the best mixture with total absorbance capacity and photostability statistically equal to the AVO–ONX mixtures but with statistically superior broad spectrum UV absorbance compared to AVO–ONX and AVO–FSG mixtures. The natural, vegetable oil‐based FSG can be substituted on an equimolar bases for ONX in mixtures with AVO to produce formulations with similar to superior efficacy.